The Well-Being of Agricultural Animals - Curtis, Stanley E.; Baker, Frank H.; Looney, Jake W.; Siegel, Paul B.; Thompson, Paul B.; Albright, Jack L.; Craig, James V.; Grandin, Temple; Guither, Harold D.; McGlone, John J.; McKean, James D.; Riskowski, Gerald L.; et al. (Council for Agricultural Science and Technology (CAST), 1997)
Concern for the welfare of farm animals is mounting in the United States. Although many of the issues of agricultural animal welfare probably will be resolved politically, the CAST task force recommends that scientists become involved in clarifying the issue.